“Gender” in International Human Rights Law: Theory and Practice - A. Kh. Abashidze; O. K. Goncharenko (Московский журнал международного права, 2022)
INTRODUCTION. The institute for the protection of women both at international and national levels taking into account the ongoing discussions on the term “gender” is considered in the article. The authors examine the distinction between concepts “sex”, “gender” and “gender identity”, enshrined in international legal acts and documents, the States’ positions and approaches to their use, including on the example of the implementation of the Council of Europe Convention on Preventing and Combating Violence Against Women and Domestic Violence, better known as the Istanbul Convention.MATERIALS AND METHODS. During the research the authors used diﬀerent international legal documents, including international treaties, recommendations of the United Nations treaty bodies, reports of the special rapporteurs and international experts, outcome documents of international conferences, as well as doctrinal sources and national legislation of foreign countries. The study was carried out based on general scientiﬁc and special scientiﬁc methods. The methods of legal modeling and forecasting were widely used in the analysis in order to deﬁne prospects for possible future studies and development of international human rights law on the protection of women from violence and domestic violence.RESEARCH RESULTS. Demonstrating diﬀerent approaches to understanding the term “gender” in protecting women from violence and domestic violence, implemented by international organizations and States, the authors examined factors that inﬂuence the position of national authorities of a number of countries when considering the possibility of accession or ratiﬁcation of the core international legal acts in this area on the example of the Council of Europe Convention on Preventing and Combating Violence Against Women and Domestic Violence.DISCUSSION AND CONCLUSION. The authors came into conclusion that the problems of violence against women and domestic violence should be viewed through the lens of gender equality concept, which does not entail the elimination of biological diﬀerences between two sexes and does not encourage women and men to change their social roles. The article stresses the need for an internationally agreed deﬁnition of the term “gender” in order to strengthen the legal and institutional mechanisms for a more efﬁcient practical implementation of measures to combat violence against women and domestic violence.